2019
DOI: 10.1002/jbio.201800293
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental conditions in bovine bone ablation by ultrafast laser

Abstract: Ultrafast lasers are promising tools for surgical applications requiring precise tissue cutting. Shallow ablation depth and slow rate as well as collateral damage are common barriers limiting the use of laser in clinical applications. Localized cooling with water and/or air jet is known to reduce collateral thermal damage. We studied the influence of environmental conditions including air, compressed air flow, still water and water jet on ablation depth, ablation rate and surface morphology on bovine bone samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Most authors performed their experimental laboratory research on animal bones with the purpose to determine the laser effects on bone tissues (16)(17)(18)(19)(20). The results of most studies revealed reduced thermal effects, minimal damage to adjacent tissue around the ablation crater, and more regular smooth incisions, promoting bone repair.…”
Section: Resultsmentioning
confidence: 99%
“…Most authors performed their experimental laboratory research on animal bones with the purpose to determine the laser effects on bone tissues (16)(17)(18)(19)(20). The results of most studies revealed reduced thermal effects, minimal damage to adjacent tissue around the ablation crater, and more regular smooth incisions, promoting bone repair.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafast lasers are well known for their use in precision ablation and micromachining. Virtually any material can be ablated by ultrafast lasers, with applications in, but not limited to, metal [52], semiconductor [53], dielectric [54], and bone [55] micromachining, thin film machining [56], microfluidic structure fabrication [57], microelectromechanical systems (MEMS) device manufacturing [58], laser-induced breakdown spectroscopy (LIBS) [59], and implant modification [60]. There are many ablation mechanisms that have been proposed, and they occur under different irradiation parameters and in different materials, as often modelled by hydrodynamic and molecular dynamics simulations [61,62].…”
Section: Ultrashort Pulse Ablationmentioning
confidence: 99%
“…Despite the advances in vibration assisted manufacturing, micro-hole drilling on skull for minimally invasive neural intervention was rarely reported. Meanwhile, researchers also investigated the possibility of laser drilling on bone [10][11][12]. However, it is difficult to accurately monitor the laser drilling terminal in physiological conditions and over-cutting would cause serious damage to brain tissue [10].…”
Section: Introductionmentioning
confidence: 99%